Pengaruh Keterlibatan Ayah (Father Involvement) Terhadap Empati Pada Remaja Yang Memiliki Saudara Kandung Autisme (Siblings With Autism) - Syifa, Anggreana Lailatus; Rizkyanti, Charyna Ayu (Universitas Islam Negeri Raden Intan Lampung, 2022)
Empathy is the ability to understand the emotional state of others which makes it easier for teenagers to understand and accept the situation of their autistic siblings, improve relationships and minimize conflict. This study aims to determine the role of father involvement on empathy in adolescents who have autistic siblings. A total of 88 adolescents who have siblings with autism were taken using the snowball sampling technique. There were two scales, father involvement scale (35 items) and Basic Empathy Scale (20 items. By using simple regression analysis techniques, the results showed R2 = 0.564 with a value of T = 10.538 with p = 0.000 (p <0.01), means there is a significant positive correlation between father involvement and empathy in adolescents who have siblings with autism. This research underlines the importance of father involvement to develop empathy for sibling interaction, particularly they who have autism sibling.Keywords: Father's Involvement, Empathy, Sibling with autism.